ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI FURNITUR DARI ALUMUNIUM DI KOTA PEKANBARU - Marjelina, Sermy; Kornita, Sri Endang; Pailis, Eka Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at the Furniture Industry of aluminum in the city of Pekanbaru. This study aims to determine the factors that influence the production of Furniture Industry of Aluminum and how the influence of capital, labor and raw materials for industrial production of aluminum furniture in the city of Pekanbaru. The approach of this research is using quantitative descriptive approach. The data used in this study are primary data and secondary data. Population Industry aluminum used in this study amounted to 20 units of business or industry. Data analysis method used in this research is multiple linear regression in the process by using SPSS for Windows version 21.0. The results showed that in partial labor (X2) and variable raw material (X3) has a significant effect on the production variable (Y), while capital variable (X1) does not affect production. Simultaneously test results obtained value Fhitung (38,212)> F table (3.634) or significance value less than 5% alpha (0.000 <0.05). It is concluded that together there is a real impact on capital variable (X1), Labor (X2), Raw Materials (X3), to the production variable (Y) with a margin of error of 5%level.Regression analysis produces the coefficient of determination (R2) of 0.878. This means that the variables that affect the production of Furniture Industry of Aluminum in Pekanbaru can be explained by the variable Capital, Labor, and Raw Materials amounted to 87,8%. While the remaining 12,2% is influenced by other factors not examined.Keywords : Capital, Labor, and Raw Materials